Postcards from the frontline: a traverse through Australia’s Antarctic policy - Anthony Press (2022)
POLICY DEVELOPMENT CAN be an arcane process, so I’ll begin this exploration of Australian Antarctic policy on a lighter note. After the 2013 election I was commissioned by the Australian Government to prepare a report on Australia’s Antarctic strategic interests. In October 2014 Greg Hunt, the then Minister for the Environment, was in Hobart to publicly release that report, Australia’s 20 Year Australian Antarctic Strategic Plan. In the heat (or perhaps it was the excitement?) of the moment, Hunt departed from his prepared notes to discuss the protection of walruses. It was one of those moments when the only thing you do is to try to keep a straight face. Tasmanian journalist Andrew Darby – a specialist in Antarctic affairs and conservation – was somewhere in my line of sight; I made sure I made no eye contact.